2013
DOI: 10.1080/13557858.2012.730609
|View full text |Cite
|
Sign up to set email alerts
|

Perceived racial/ethnic discrimination, problem behaviors, and mental health among minority urban youth

Abstract: Objectives We examined perceived frequency and intensity of racial/ethnic discrimination and associations with high-risk behaviors/conditions among adolescents. Design With surveys from 2,490 primarily low socioeconomic status, racial/ethnic minority adolescents, we used regression analysis to examine associations between racial/ethnic discrimination and behavioral health outcomes (alcohol use, marijuana use, physical aggression, delinquency, victimization, depression, suicidal ideation, and sexual behaviors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
101
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 130 publications
(105 citation statements)
references
References 40 publications
4
101
0
Order By: Relevance
“…Tobler and colleagues (2013) found perceived racial-ethnic discrimination to be associated with multiple high-risk behaviors among an urban, racial-ethnic minority youth sample. Similar to our findings, race/ethnicity was not a significant moderator of the observed associations.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Tobler and colleagues (2013) found perceived racial-ethnic discrimination to be associated with multiple high-risk behaviors among an urban, racial-ethnic minority youth sample. Similar to our findings, race/ethnicity was not a significant moderator of the observed associations.…”
Section: Discussionmentioning
confidence: 89%
“…In a Latino adolescent sample, Okamoto and colleagues (2009) found an association between perceived discrimination and smoking, alcohol, marijuana, inhalants, and binge drinking. In the limited number of studies with diverse samples, discrimination was significantly associated with negative health outcomes, yet race was not a significant moderator (e.g., Choi, Harachi, Gillmore, & Catalano, 2006; Tobler et al, 2013). …”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…In addition to these proximal and primary outcomes, we included measures of hypothesized intervention effect moderators, including demographic characteristics (i.e., gender; race/ethnicity and tribal membership; family com- Tobler et al, 2013;Wolfe & Kimerling, 1997); Depression (6 items; Kandel & Davies, 1982); and AI (3 items) and White American or Anglo (3 items) Cultural Identity (Oetting & Beauvais, 1991). (A copy of the survey is available on request from the fi rst author.…”
Section: Theoretical Framework and Survey Developmentmentioning
confidence: 99%
“…Recently, research in the UK and US identified low socio-economic class and poverty as the main factors of mental illness (Tobler et al, 2013, Lê Cook et al, 2011, similar to studies in the US examining ethnic minority populations in substance misuse (Field et al, 2012, Molina et al, 2012. The US research focus was on socio-economic factors, making drug users from poorer backgrounds more vulnerable to contracting HIV and Hepatitis C.…”
Section: Previous Researchmentioning
confidence: 94%